Fuzzy modeling of the effects of irrigation and water salinity in harvest point of tomato crop. Part Ii: Application and interpretation - Neto, Daniel dos S. Viais; Cremasco, Camila P. [UNESP]; Bordin, Deyver [UNESP]; Putti, Fernando F. [UNESP]; Silva Junior, Josué F.; Filho, Luís R.A. Gabriel [UNESP] (FapUNIFESP (SciELO), 2019)
Tomato, the most popular greenery, is characterized by being a demanding crop in water and when in prolonged and severe drought, has limitations in its growth and reduction in productivity. In addition, this vegetable is affected by excess salinity in the water, which causes leaf wilting, apex and leaf edges burn until their death. Such effects generally are studied using statistical analysis, but there are mathematical theories that allow finer adjustments, highlighting among them, the fuzzy logic. The objective of this study was to evaluate the effects on the growth and yield of hybrid tomato from different water tensions in the soil and different salinity doses in the irrigation at 120 days after sowing using fuzzy modeling. It was used data from an experiment that was conducted in the experimental area at the School of Agriculture of São Paulo State University (UNESP) in Botucatu-SP. The input variables of the fuzzy systems were irrigation and salinity, while the output variables elected were the biometric analysis and productivity that showed statistically significant differences. Analyses of the effects of irrigation and salinity were performed by means of three-dimensional graphics and the output variables contour maps. The variables studied here showed higher values, with exception of plant height for treatment with irrigation in field capacity and water salinity zero.
Keywords: Drought; Fuzzy logic; Hydro potential; Salt stress